KONTRIBUSI MOTIVASI DAN PEMANFAATAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR DASAR LISTRIK ELEKTRONIKA - Boy Ichsan Herianto; Putra Jaya (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This study aims to determine the Contribution of Learning Motivation and Utilization of Learning Facilities Against Basic Electrical and Electronic Learning Outcomes Grade X Students of Audio Video Engineering Skills Program at SMK Negeri 5 Padang. The population in this study amounted to 63 students. This type of research is correlational descriptive. In this study using Simple Random Sampling with a total of 56 students. Data Learning outcomes were obtained from Elementary and Electrical subject teachers at SMK Negeri 5 Padang. Meanwhile Motivation Learning Data and Learning Facilities Utilization obtained by using a questionnaire with a Likert scale that has been tested for validity and reliability. The results of data analysis showed: (1) Motivation to Learning and Utilization of Learning Facilities together contributed 36.24% to learning outcomes; (2) Learning Motivation contributes 7.95% to learning outcomes; (3) Utilization of Learning Facilities contributes 25.50% to learning outcomes. So it can be concluded that the motivation to learn and use learning facilities contributes to the learning outcomes of basic electricity and electronics at SMK Negeri 5 Padang.Keywords: Learning Motivation, Utilization of Learning Facilities, Learning Outcomes